Influence of agitation intensity on solution stability for rapidly grown KDP crystal through theoretical and experimental research. (September 2020) - Liu, Guangxia; Wang, Duanliang; Cui, Zixiao; Shen, Chuanying; Xu, Meirong; Meng, Fan; Yao, Shengkun; Wang, Shenglai
Highlights: Influence of agitation intensity on solution stability was explored for rapidly grown KDP crystal. Growth rate increases with the increase of rotation speed less than 100 r/min. Solution stability decreases with increase of agitation intensity by MSZW results. Characteristics of turbulent dissipation and vorticity were analyzed in detail by simulation. The variation of vorticity has a substantial impact on solution instability. Abstract: For rapid growth of KDP crystal, the influence of agitation intensity on solution stability was investigated by altering rotation speed in crystalline procedure. Based on the experiments, the results demonstrate that rotation speed has a great influence on growth rate, which increases with increase of rotation speed as is no more than 100 r/min. The corresponding metastable zone widths (MSZW) indicate that solution stability decreases with the agitation intensity increasing, while introducing a seed into the growing solution has little effect on MSZW. Combined with numerical simulation, the dependences of rotation speeds on turbulent dissipation and vorticity imply that growth solution with a laminar state has a better stability and a stronger ability to resist spontaneous crystallization at lower speeds. With increasing of rotation speeds ranging from 22 to 106 r/min, the growth solution is transformed from laminar to turbulent state causing the decrease of solution stability, while the turbulent dissipation rate increases gently with increasing of rotation speed. Furthermore, the vortex magnitude increases with rising of rotation speed, and an obvious variation of vorticity has a substantial impact on solution instability, especially at high-speed larger than 200 r/min. Thus, appropriately reducing speed is an effective way to maintain the stability of growing environment and beneficial to realize rapidly grown KDP crystal with high-quality.